Induction of somatic DNA damage as measured by single cell gel electrophoresis and point mutation in leaves of tobacco plants - Gichner, T; Plewa, M J (Mutation research, 1998)
The induction and measurement of DNA damage in nuclei of plant tissues is a new area of study with the alkaline single cell gel electrophoresis/comet assay. Methods to isolate plant cell nuclei cause high levels of DNA damage which are detected by the comet assay. We developed a method to isolate nuclei from leaf tissue of Nicotiana tabacum (a1+/a1; a2+/a2) in a modified Sörensen buffer that resulted in constant, low tail moment values for the negative controls. After treating intact tobacco plants with 1-8 mM ethyl methanesulfonate (EMS) we obtained a direct concentration-response with an average median tail moment of 65.9+/-4.4 micro(m) for plants exposed to the highest EMS concentration as compared to the median control tail moment value of 4.1+/-0.8. We found that the highest resolution was obtained with electrophoretic conditions of 0.74 V/cm at 300 mA for 20 min. Multiple leaves could be analyzed per plant within each treatment group and the tail moments were not significantly different. Tobacco seedlings were treated with EMS in the same manner as used for the comet assay and mutations were induced in the leaf primordia. The mean mutant frequency for the control was 1.46+/-0.20 mutant sectors/leaf. The mutant frequency increased in a concentration dependent manner; the mutant frequency induced by 8 mM EMS was 37.89+/-2.37 mutant sectors/leaf. The comet tail moment values and the leaf mutant frequency were highly correlated (r=0.98). The genetic response factor was calculated by the ratio of the difference in the response within the linear portion of each concentration-response curve divided by the slope of the curve. The genetic response factor for the tail moment was 7.82 while the value for mutation induction was 7.76. In this paper we describe a sensitive method with high resolution to apply the alkaline comet assay to plant leaves. The comet assay response was compared to that of induced point mutation. With this sensitive method for nuclei isolation from plant leaves, the alkaline SCGE assay could be incorporated into in situ plant environmental monitoring.
Keywords: elektroforéza v agarovém gelu; DNA Damage; Mutagenicity Tests; DNA, Plant; Ethyl Methanesulfonate; listy rostlin; Nicotiana; ethylmethansulfonát; Plant Leaves; mutageny; testy genotoxicity; Plants, Toxic; Electrophoresis, Agar Gel; poškození DNA; Point Mutation; DNA rostlinná; bodová mutace; Mutagens; jedovaté rostliny; tabák